Pengaruh Layanan Samsat Corner, Kesadaran Wajib Pajak, Sosialisasi Perpajakan dan Kualitas Pelayanan pada Kepatuhan Wajib Pajak Kendaraan Bermotor - Susanti, Laila; Ery Setiawan, Putu (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This research was conducted at the Joint Office of SAMSAT Denpasar. The number of samples used in this study were 100 respondents with a sampling technique that is proportionate stratified random sampling method. Data collection in this study was conducted by a questionnaire method with data analysis technique used is multiple linear regression analysis. The results showed that SAMSAT corner service, taxpayer awareness, tax socialization, and service quality had a positive effect on motor vehicle taxpayer compliance. This means that the better SAMSAT corner service, awareness of taxpayers, tax socialization, and quality of service will also increase motor vehicle taxpayers compliance in terms of meeting their tax obligations. Keywords : SAMSAT Corner Service; Taxpayer Awareness; Tax Socialization; Service Quality; Motor Vehicle Taxpayer Compliance.